1979
DOI: 10.1111/j.1532-5415.1979.tb01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Incidence of Endometrial Cancer among Postmenopausal Women Treated with Progestogens*

Abstract: A prospective study begun in 1976 to determine the incidence of endometrial cancer in postmenopausal women was undertaken because of the adverse publicity alleging an increased risk of endometrial cancer in women receiving estrogen therapy. A retrospective study for the year 1975 was added. During 8,170 patient-years in the 3-year 1975-1977 period, 14 endometrial malignancies were diagnosed, for an annual incidence of 1.7 per 1,000 women. During the 3,792 patient-years of observation of estrogen-progestogen us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…2 Unopposed estrogen therapy increases the risk of endometrial cancer,3 whereas combined estrogen/gestagen therapy may eliminate this risk. 4 The metabolic side effects of estrogen therapy are influenced by the type5 and dosage6 of estrogen used and by the route of 7 administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Unopposed estrogen therapy increases the risk of endometrial cancer,3 whereas combined estrogen/gestagen therapy may eliminate this risk. 4 The metabolic side effects of estrogen therapy are influenced by the type5 and dosage6 of estrogen used and by the route of 7 administration.…”
mentioning
confidence: 99%
“…13 The aim of the present placebo-controlled study was to examine the long-term effect of 14 This method, which requires a 90 min rectilinear scanning procedure, has an accuracy of approximately 1 kg or 2.5% for LBM and that of 5% for FM measurement in a normal adult female. 4 Blood samples were taken between days 16 and 22 of the cycle, i.e., during gestagen treatment. All participants were examined in the morning after an overnight fast and tobacco abstinence, 24 hr after the last hormone dose.…”
mentioning
confidence: 99%
“…Most of these studies were conducted in the USA and most concern the drug Premarin (conjugated equine oestrogens). Some cohort studies have also been reported: by and large they have supported the results of the case-control studies, but the numbers of women with endometrial cancer have been small (Gambrell et al 1979, Persson 1983, Hunt & Vessey 1984. Some important features of the association between replacement therapy and endometrial cancer are (1) the risk is related to oestrogen dose and to duration of use; (2) the risk declines after discontinuation of treatment; (3) cancers occurring in women using oestrogens tend to be less advanced at detection and of more favourable grade than cancers occurring in other women -their prognosis is correspondingly more favourable; and (4) addition of a progestogen to the oestrogen during each 'cycle' of therapy may well reduce, eliminate or even reverse the risk (see Vessey & Bungay 1982).…”
mentioning
confidence: 73%
“…One prospective study38 showed a 2:1 risk from estrogen treatment alone, while for estrogen/progestogen therapy a consistent lack of association was demonstrated. 38 39 No study has detected the correct temporal relation between therapy and endometrial carcinoma, although the correct dose-response gradient has been demonstrated for estrogen alone. 37 The contention that ERT might lead to endometrial carcinoma makes epidemiological sense, since an increased incidence was observed when ERT prescriptions increased.40 There was no increase in mortality, however, lending credence to the view that hyperplasia is difficult to distinguish from Stage I or II endometrial carcinoma.27 The association is nevertheless credible biologically, since glandular endometrial hyperplasia can be induced in animals given estrogen.41…”
Section: Therapiesmentioning
confidence: 99%